Roles of CRAC channel in cancer: implications for therapeutic development. Issue 5 (2nd September 2020) - Khan, Husain Yar; Mazahir, Iqra; Reddy, Shriya; Fazili, Farzeen; Azmi, Asfar Sohail
ABSTRACT: Introduction: The Ca2+ release-activated Ca2+ (CRAC) channel, composed of Orai and STIM proteins, represents one of the main routes of Ca 2+ entry in most nonexcitable cells. There is accumulating evidence to suggest that CRAC channel can influence various processes associated with tumorigenesis. Overexpression of CRAC channel proteins has been observed in several types of cancer tissues and cells, indicating that blocking CRAC channel activated Ca 2+ influx can have therapeutic benefits. Areas covered: In this review, we have focused on the molecular composition and activation mechanism of CRAC channel as well as the myriad roles this Ca 2+ channel play in various cancers. We further describe relevant information about several efforts aimed at developing CRAC channel blockers and their likely implications for cancer therapy. We have extensively utilized the available literature on PubMed to this end. Expert opinion: The possibility of targeting CRAC channel mediated Ca 2+ entry in cancer cells has generated considerable interest in recent years. Use of CRAC channel blockers in cancer preclinical studies and clinical trials has been relatively limited as compared to other diseases. The future lies in developing and testing more potent and selective drugs that target cancer cell specific CRAC channel proteins, hence opening better avenues for cancer therapeutic development.